Maize Yield Under Fertilization With Bio-Stimulants, Sulfur, and Zinc in the State of Paraíba, Brazil - Silva, Helton Devison de Lima; Silva, Antônio Veimar da; Silva, João Henrique Barbosa da; Silva, Edson de Souza; Neto, José Fidelis dos Santos; Soares, Misael Mendes; Silva, Carla Michelle da; Mielezrski, Fabio (Journal of Agricultural Studies, 2021)
Maize (Zea mays) is a cereal widely used in human and animal feeding worldwide, with great socioeconomic importance. This study aimed to evaluate the growth, productivity, and absorption of macro and micronutrients of maize under the application of biostimulant, sulfur, and zinc in a Gleisolo Háplico soil in a microclimate region of the semiarid state of Paraíba, Brazil. The experiment was carried out in a complete randomized block design, a 2x2x2 factorial scheme with eight treatments, and four replications was used. The first factor corresponded to treatment with biostimulant (Presence and absence); the second to sulfur (Presence and absence); and the latter to zinc (Presence and absence). Growth, yield, and macro and micronutrient absorption data were evaluated. Data were submitted to analysis of variance and the means compared by the Tukey test at 5% probability. The number of rows per ear and ear diameter responded positively when the biostimulant was used. Maize under foliar fertilization with zinc nitrate did not show yield increase. The application of sulfur promoted an increase in almost all variables, including yield. The combined application of the three products influenced only the number of rows per ear. The application of sulfur separated or together with biostimulant provided an increase in the absorption of some nutrients by the leaf such as copper, N and K. As a result of fertilization with sulfur, which provided an increase in leaf absorption, mainly of N, also promoted a significant increase in all student variables, including grain productivity.